Predictive factors for positive disco-vertebral biopsy culture in pyogenic vertebral osteomyelitis, and impact of fluoroscopic versus scanographic guidance - Diffre, Caroline (BMC Infect Dis, 2020)
BACKGROUND: The aims of this study were to identify the predictive factors for microbiological diagnosis through disco-vertebral biopsy (DVB) in patients with pyogenic vertebral osteomyelitis (PVO) and negative blood cultures, and compare the performance of DVB under fluoroscopic versus scanographic guidance. METHODS: We performed a cohort study comparing positive and negative DVB among patients with PVO. All cases of PVO undergoing a DVB for microbiological diagnosis in our center were retrospectively reviewed. Infections due to Mycobacterium tuberculosis, infections on foreign device, and non-septic diseases were excluded. Anamnestic, clinical, biological, microbiological, as well as radiological data were collected from medical charts thanks to a standardized data set. RESULTS: A total of 111 patients were screened; 88 patients were included. Microbiological cultures were positive in 53/88 (60.2%) patients. A thickening of the paravertebral tissue ≥10 mm on magnetic resonance imaging (MRI) in axial MR scans was a predictive factor of DVB microbiological positivity (52.4% vs. 13.3%; p = 0.006; OR = 5.4). Overall, 51 DVB were performed under fluoroscopic guidance and 37 under scanographic guidance. Considering lumbar DVB, 25/36 (69.4%) of cases yielded positive results under fluoroscopic guidance versus 5/15 (33.3%) under scanographic guidance (p = 0.02; OR = 4.4). No adverse event linked to DVB was notified. CONCLUSION: Every patient with PVO and negative blood cultures should undergo a DVB. A thickening of the paravertebral tissue ≥10 mm on MRI is associated with a higher rate of positive DVB culture. A lumbar DVB under fluoroscopic guidance is more sensitive than under scanographic guidance to identify the micro-organism involved.